Museo de cera: una forma de enseñanza de la sífilis en Chile a principios del siglo XX - Valenzuela A., Fernando; Saavedra R., Daniela; Zemelman D. , Viviana (Revista Hospital Clínico Universidad de Chile, 2009)
At the beginning of the twentieth century, Dermatology’s teaching was more complex than today, heavily based on fine semiology. During the last centuries, the art of moulage preparation evolved from 2-dimensional images in black and white to 3-dimensional figures with color and relief, realistic representations of diseased parts of the human body, essential in a morphological and descriptive discipline. The technique of wax figures in Dermatology began in the nineteenth century in France, at St. Louis Hospital. Subsequently, Olavide created a wax museum at San Juan de Dios Hospital in Spain. In Chile, wax moulages of syphilis and other sexually transmitted diseases were used for the teaching of Dermatology by the National Health Service. The moulages were carved by Mrs. Anita Lagarrigue and designed by Professor Dr Luis Prunés (Chair of Dermatology at Saint Vincent de Paul Hospital) in the 1940’s. Until today, we have found 15 wax moulages, partially preserved in wooden and glass boxes in the Dermatology Department at the Clinical Hospital of the University of Chile (former Saint Vincent de Paul Hospital). This wax figures collection represents a significant work of art and reflects a very important part of the history of Chilean Dermatology.